Superionic Conductivity in Ceria-Based Heterostructure Composites for Low-Temperature Solid Oxide Fuel Cells - Zhang, Yifei; Liu, Jingjing; Singh, Manish; Hu, Enyi; Jiang, Zheng; Raza, Rizwan; Wang, Faze; Wang, Jun; Yang, Fan; Zhu, Bin (Nano-Micro Letters, 2020)
Ceria-based heterostructure composite (CHC) has become a new stream to develop advanced low-temperature (300–600 °C) solid oxide fuel cells (LTSOFCs) with excellent power outputs at 1000 mW cm−2 level. The state-of-the-art ceria–carbonate or ceria–semiconductor heterostructure composites have made the CHC systems significantly contribute to both fundamental and applied science researches of LTSOFCs; however, a deep scientific understanding to achieve excellent fuel cell performance and high superionic conduction is still missing, which may hinder its wide application and commercialization. This review aims to establish a new fundamental strategy for superionic conduction of the CHC materials and relevant LTSOFCs. This involves energy band and built-in-field assisting superionic conduction, highlighting coupling effect among the ionic transfer, band structure and alignment impact. Furthermore, theories of ceria–carbonate, e.g., space charge and multi-ion conduction, as well as new scientific understanding are discussed and presented for functional CHC materials. HIGHLIGHTS • Ceria-based heterostructure composite for novel semiconductor-ionic fuel cells. • Superionic conduction at interfaces is associated with the crossover of band structure. • Band alignment/bending resultant built-in field plays a significant role in superionic conduction.